The Co-Surgeon Model for Microsurgical Free Flaps: A Survey of Perspectives and Utility - Giannas, Emmanuel; Alba, Brandon; Harmon, Kelly; Fritsch, Annie; Kurlander, David; Shenaq, Deana; Kaoutzanis, Christodoulos; Reid, Christopher; Matros, Evan; Mehrara, Babak; Kokosis, George (Journal of Reconstructive Microsurgery, 2025)
Reconstructive microsurgery remains a demanding field, requiring technical expertise and long operating hours. This places microsurgeons at increased risk of dissatisfaction and burnout. The co-surgeon model has been developed to mitigate these challenges. This study was designed to evaluate microsurgeon perspectives on the characteristics and impact of the co-surgeon model for microsurgical free flaps.An electronic anonymous survey was distributed via email to attending microsurgeon members of the American Society of Reconstructive Microsurgeons. The survey collected various demographic and practice-related information including Likert scale questions to assess microsurgeon perspectives on the utility of the co-surgeon model.A total of 862 microsurgeons received the survey, with 102 responses available for analysis. The average age of respondents was 46.6 (± 9.7) years. Most of the microsurgeons were male (71%) practicing in the United States (93%), with 74.5% of respondents utilizing a co-surgeon model in their practice. Bilateral breast flaps were the most common microsurgical procedure performed using a co-surgeon (85%), followed by head and neck free flaps (60%), with immediate lymphatic reconstruction being the least common (3.1%). On the day of the co-surgery case, the co-surgeon was more likely than the primary surgeon to have additional cases (68.4 and 36.4%, respectively), with the additional cases being rarely free flaps. More than 80% of microsurgeons stated that the co-surgeon model improves “very much” or “quite a bit” operative efficiency and duration, as well as surgeon well-being and career longevity.This study provides new insight into the utility of using a co-surgeon for free flap reconstruction by demonstrating that approximately 80% of microsurgeons have a positive perception of the model's impact on procedure efficiency, operative time, surgeon well-being, and career longevity. Therefore, adopting a co-surgeon model for microsurgical free flap reconstruction may be useful in reducing burnout and promoting well-being among microsurgeons.
Keywords: co-surgeon; perioperative case; free flap reconstruction; reconstructive microsurgery